2002
DOI: 10.1080/00365540110080773
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility to Quinolones of Francisella tularensis subspecies tularensis

Abstract: Francisella tularensis is a potent pathogen and a possible bioterrorism agent, for which quinolones offer promising new therapeutic options. There are, however, no data on the susceptibility to quinolones of natural isolates of F. tularensis tularensis, the highly virulent North American subspecies. In the present study, 8 isolates of F. tularensis tularensis, originating from 8 different states of the USA, and 16 US isolates of F. tularensis holarctica were tested. All 24 isolates showed MIC values < or = 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 12 publications
3
31
0
4
Order By: Relevance
“…The E test strips (AB Biomerieux, Solna, Sweden), including the 13 antibiotics listed in Table 1, were placed on these plates. After incubation at 379 C for 2 days, the minimum inhibitory concentration (MIC) was determined as the MICs of the quality control strains (E. coli and S. aureus) and F. tularensis LVS were similar to the reference MICs found in the instructions of the E test, as reported by Valade et al (9), and MICs reported previously (7,10,15) (Table 1). Using this assay system, ciprofloxacin, doxycycline, erythromycin, and gentamicin effectively inhibited the growth of all isolates with MIC ranges of 0.003-0.023, 0.094-1.5, 0.094-1.5, and 0.023-0.5 mg/L, respectively (Table 2).…”
mentioning
confidence: 82%
“…The E test strips (AB Biomerieux, Solna, Sweden), including the 13 antibiotics listed in Table 1, were placed on these plates. After incubation at 379 C for 2 days, the minimum inhibitory concentration (MIC) was determined as the MICs of the quality control strains (E. coli and S. aureus) and F. tularensis LVS were similar to the reference MICs found in the instructions of the E test, as reported by Valade et al (9), and MICs reported previously (7,10,15) (Table 1). Using this assay system, ciprofloxacin, doxycycline, erythromycin, and gentamicin effectively inhibited the growth of all isolates with MIC ranges of 0.003-0.023, 0.094-1.5, 0.094-1.5, and 0.023-0.5 mg/L, respectively (Table 2).…”
mentioning
confidence: 82%
“…Bu dozda doksisiklin kullanılmasıyla serumda ortalama 4 mg/lt ilaç konsantrasyonuna ulaşılmaktadır (33). Doksisiklinin F. tularensis için minimum inhibitör konsantrasyonu (MİK)'nun 0.25-2 mg/lt arasında olmasına dayanarak serumdaki bu ilaç konsantrasyonu optimum antibakteriyel aktivite için yeterli görülmektedir (24)(25)(26)(27)34,35).…”
Section: Tetrasiklinlerunclassified
“…Kinolonların alt tür tularensis kökenlerine karşı MİK değerleri alt tür holarctica izolatlarına benzer olarak bulunmuştur (34,35). Ancak, kinolonların (siprofloksasinin) alt tür tularensis infeksiyonunun tedavisindeki etkinliğine dair çok az veri bulunmaktadır.…”
Section: Kinolonlarunclassified
See 2 more Smart Citations